Subjective attitudes moderate the social connectedness in esports gaming during COVID-19 pandemic: A cross-sectional study - Shan, Dan; Xu, Jilai; Liu, Tongyu; Zhang, Yanyi; Dai, Ziyun; Zheng, Yuandian; Liu, Chang; Wei, Yuanning; Dai, Zhihao (Frontiers in Public Health, 2023)
During the COVID-19 pandemic, esports has become a valuable intervention for young people craving social connections. Although many previous studies suggested the beneficial role of video games in boosting social ties, few studies explored it in the context of esports gaming and COVID-19. Therefore, understanding the impacts of esports gaming on social connections during the pandemic era is crucial. We conducted a nationwide online questionnaire survey through the Credamo platform among 550 Chinese young adults in the present study. The Social Connectedness Scale-Revised was used to assess the levels of social connectedness of participants. 453 participants were finally included in analysis after data cleaning. The effective response rate was 82.4%. Regarding our results, the communication frequency of participants during esports gaming as a separate factor was statistically significantly and negatively associated with social connectedness scores (β = -0.13, p < 0.05). However, when the moderating effect of subjective attitude toward esports gaming on communication frequency in collectively impacting social connectedness was considered, the association between communication frequency and social connectedness scores was turned into the opposite direction to a large extent (β = 0.35, p < 0.001). Our primary finding revealed that possessing a positive mindset in esports gaming exerts an indispensable role in boosting social connectedness. Overall, our study provided supporting evidence for the benefits of online gaming on social connections. Practical recommendations for appropriate and healthy patterns of esports gaming for pursuing optimal levels of social connectedness, especially during the pandemic era or future similar circumstances, were also structured. Hopefully, our study can encourage future and further psychological intervention and investigation regarding esports.